Coating Pt–Ni Octahedra with Ultrathin Pt Shells to Enhance the Durability without Compromising the Activity toward Oxygen Reduction. Issue 16 (27th July 2016) - Park, Jinho; Liu, Jingyue; Peng, Hsin‐Chieh; Figueroa‐Cosme, Legna; Miao, Shu; Choi, Sang‐Il; Bao, Shixiong; Yang, Xuan; Xia, Younan
Abstract: We describe a new strategy to enhance the catalytic durability of Pt–Ni octahedral nanocrystals in the oxygen reduction reaction (ORR) by conformally depositing an ultrathin Pt shell on the surface. The Pt–Ni octahedra were synthesized according to a protocol reported previously and then employed directly as seeds for the conformal deposition of ultrathin Pt shells by introducing a Pt precursor dropwise at 200 °C. The amount of Pt precursor was adjusted relative to the number of Pt–Ni octahedra involved to obtain Pt–Ni@Pt1.5L octahedra of 12 nm in edge length for the systematic evaluation of their chemical stability and catalytic durability compared to Pt–Ni octahedra. Specifically, we compared the elemental compositions of the octahedra before and after treatment with acetic and sulfuric acids. We also examined their electrocatalytic stability toward the ORR through an accelerated durability test by using a rotating disk electrode method. Even after treatment with sulfuric acid for 24 h, the Pt–Ni@Pt1.5L octahedra maintained their original Ni content, whereas 11 % of the Ni was lost from the Pt–Ni octahedra. After 10 000 cycles of ORR, the mass activity of the Pt–Ni octahedra decreased by 75 %, whereas the Pt–Ni@Pt1.5L octahedra only showed a 25 % reduction. Abstract : Skin deep : Conformal Pt shells with a thickness of only 1–2 atomic layers are deposited on Pt–Ni octahedra to obtain core–shell catalysts with both high mass activity and durability toward the oxygen reduction reaction.